La evolución de las imágenes del coronavirus en los informativos de las televisiones españolas y su relación con las imágenes científicas del virus - Dr. Jaime LÓPEZ-DÍEZ,Dra. Gema BONALES DAIMIEL,Dr. Isidro JIMÉNEZ GÓMEZ,Dr. Francisco-José GARCÍA-RAMOS (Fonseca, Journal of Communication, 2023)
The main goal of this study is to analyze the characteristics of the image of the SARSCoV-2 in the Spanish television news programs,and its evolution, as well as their relation with the scientific images of the virus they were based upon. Thus, a sample of images from four television networks (RTVE, Antena TV, La Sexta y Cuatro), in 2020 and 2021, have been studied.